1985
DOI: 10.3168/jds.s0022-0302(85)81183-8
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Dairy Cow Diets with Ammonium Salts of Volatile Fatty Acids

Abstract: The objective was to determine the efficacy of a blend of ammonium salts of the volatile fatty acids, isobutyric, 2-methylbutyric, isovaleric, and valeric as a supplement to diets for dairy cows. Treatments of 0 (control) or 120 (supplemented) g/cow of the blend were fed daily from approximately 3 wk prepartum through a complete lactation. Five trials were conducted concurrently with a total of 116 multiparous Holstein cows. Dietary ingredients or combinations of ingredients differed in each of the trials. Die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…Supplementation of IA increased milk fat yield by increasing milk fat content but not milk volume, and the increased milk fat content resulted from increased de novo synthesis of milk FA. Increased milk fat yield is consistent with results from most studies in which individual BCVFA, IA, or IA without valerate were fed to cows (Papas et al, 1984;Peirce-Sandner et al, 1985;Wang et al, 2019). Similar results were also observed in a study by Liu et al (2018).…”
Section: Main Effects Of Ia Within the Lf Dietssupporting
confidence: 89%
See 1 more Smart Citation
“…Supplementation of IA increased milk fat yield by increasing milk fat content but not milk volume, and the increased milk fat content resulted from increased de novo synthesis of milk FA. Increased milk fat yield is consistent with results from most studies in which individual BCVFA, IA, or IA without valerate were fed to cows (Papas et al, 1984;Peirce-Sandner et al, 1985;Wang et al, 2019). Similar results were also observed in a study by Liu et al (2018).…”
Section: Main Effects Of Ia Within the Lf Dietssupporting
confidence: 89%
“…This could be an evidence of IA stimulating milk fat synthesis because acetate supplementation can increase milk fat synthesis (Urrutia et al, 2019). Previous in vivo studies (Papas et al, 1984;Peirce-Sandner et al, 1985;Liu et al, 2018;Wang et al, 2019) also showed that supplemental IA increases fiber digestion or milk fat yield in dairy cows and could be effective in alleviating MFD.…”
Section: Introductionmentioning
confidence: 94%
“…Linear multiple regressions estimating response in milk yield and protein content: Y=a + bjX, + b 2X 2 (X, = change in RSM intake; X 2 = change in ME total -ME rsm ). valine, isoleucine and proline) has increased the milk production of dairy cows (Papas et al 1984, Peirce-Sandner et al 1985).…”
Section: Dependent Independentmentioning
confidence: 99%
“…Branched-chain VFA (BCVFA; isoacids without the straight chain, valerate) are required by microbes to synthesize branched-chain amino acids (BCAA) or branched long-chain fatty acids (FA; cell membrane constituent; Allison et al, 1962;Maczulak et al, 1981). In addition, supplementation with IA often increased fiber digestibility and milk fat yield (Peirce-Sandner et al, 1985;Wang et al, 2019). Butyrivibrio proteoclasticus, the major characterized stearate producer, was hypothesized to be very susceptible to inhibition by free PUFA and was recognized for very high C16:0 iso (derived from isobutyrate) and C17:0 anteiso (derived from 2-methylbutyrate) composition of its membranes (Hackmann and Firkins, 2015).…”
Section: Introductionmentioning
confidence: 99%